Il vino nel legno La valorizzazione della biomassa legnosa dei boschi del Chianti - Giannini, Raffaello (Strumenti per la didattica e la ricerca, 2015)
The woods have provided and still provide essential products and services for the survival of the human population, which may be identified in values of direct and indirect use. This volume presents the management strategies aimed at bringing together the sustainable use of forest ecosystems and the enhancement of the products from the wood products supply chain. In order to do so, it uses precise information on the features and on the actual 'availability' of wood volume production in the woods of the Chianti Classico area, focusing on that from chestnut and downy oak top soils. Particular attention has been paid to the production of slats for wine containers, with the aim of reviving an ancient tradition typical of the Chianti area.